Valid cardiac biomarkers. Part I - V. A. Metelskaya; N. G. Gumanova (Кардиоваскулярная терапия и профилактика, 2020)
Biomarkers are widely used for the diagnosing of diseases, evaluation of their severity, prediction of outcomes, and for monitoring the effectiveness and safety of targeted therapy. This review describes specific cardiac biomarkers approved by FDA (Food and Drug AdministrationбUSA). The list of described biomarkers is not exhaustive. In addition to the general concepts of biomarkers, definitions and classification, this Part I of the review contains data on diagnostic and prognostic biomarkers of cardiovascular diseases associated with atherosclerosis.